Corruption as a Self-Reinforcing Trap: Implications for Reform Strategy. (13th June 2020) - Stephenson, Matthew C
Abstract: Corruption is widely believed to be a self-reinforcing phenomenon, in the sense that the incentive to engage in corrupt acts increases as corruption becomes more widespread. Some argue that corruption's self-reinforcing property necessarily implies that incremental anticorruption reforms cannot be effective, and that the only way to escape a high-corruption equilibrium "trap" is through a so-called "big bang" or "big push." However, corruption's self-reinforcing property does not logically entail the necessity of a big bang approach to reform. Indeed, corruption's self-reinforcing property may strengthen the case for pursuing sustained, cumulative incremental reforms. While there may be other reasons to prefer a big bang approach to an incremental approach, this conclusion cannot be grounded solely or primarily on corruption's self-reinforcing character.